2013
DOI: 10.1186/1476-511x-12-30
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of Pelargonium graveolens L’Her essential oil on the reproductive damage induced by deltamethrin in mice as compared to alpha-tocopherol

Abstract: BackgroundExposure to the pyrethroid pesticide deltamethrin has been demonstrated to exert a wide range of effects on non-targeted organisms. The beneficial effects of geranuim essential oil (EO) as an antioxidant has been assessed in deltamethrin (DL) orally administered mice by studying whether the reprotoxicity caused by deltamethrin can be effectively combated with the geranium oil and the effects were compared to vitamin E, as the standard reference drug.ResultSixty male albino mice were divided into six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 41 publications
5
39
0
Order By: Relevance
“…This finding came in accordance with previous studies which reported that DM significantly decreased the antioxidant defense [9,15,28,29]. Also DM intoxication caused significant increase in NO concentration [ Table-2].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding came in accordance with previous studies which reported that DM significantly decreased the antioxidant defense [9,15,28,29]. Also DM intoxication caused significant increase in NO concentration [ Table-2].…”
Section: Discussionsupporting
confidence: 82%
“…Genotoxicity of a compound usually expressed as its ability to induce DNA damage, which is often essential for mutagenesis and cancer transformation [49]. In the present study DM appears to induce mutation in TP53 and H-RAS genes [ Fig-1], [Fig-2], [ [29,[50][51][52]. It increased the expression of p53 and decreased expression of Bcl-2 genes in brain [53].…”
Section: Discussionmentioning
confidence: 97%
“…Slima et al found that P. graveolens essential oil produced a strong protective effect against oxidative stress damage and that a dose of 67 mg/kg/day was sufficient to reduce protein oxidation in the testes as well as reduce oxidative stress and lipid peroxidation. The oil also improved the poor quality of the sperm [25].…”
Section: Issn 2254-6081mentioning
confidence: 98%
“…These effects when considered together lead to the conclusion that the Deltamethrin induced oxidative stress in the mice testes. When treated with the P. graveolens, the negative effects were reversed [25]. Slima et al found that P. graveolens essential oil produced a strong protective effect against oxidative stress damage and that a dose of 67 mg/kg/day was sufficient to reduce protein oxidation in the testes as well as reduce oxidative stress and lipid peroxidation.…”
Section: Issn 2254-6081mentioning
confidence: 99%
See 1 more Smart Citation